Estimating probabilities of default - Til Schuermann; Samuel Gregory Hanson (Federal Reserve Bank of New York, 2004)
We conduct a systematic comparison of confidence intervals around estimated probabilities of default (PD), using several analytical approaches from large-sample theory and bootstrapped small-sample confidence intervals. We do so for two different PD estimation methods
Keywords: G21; G28; C16; 330; cohort and duration (intensity); Insolvenz; Kreditwürdigkeit; Schätztheorie